Ab initio study on the stability of N-doped ZnO under high pressure. Issue 22 (11th March 2015) - Sha, Xiaojing; Tian, Fubo; Li, Da; Duan, Defang; Chu, Binhua; Liu, Yunxian; Liu, Bingbing; Cui, Tian
<x xml:space="preserve">Abstract</x> We perform first-principles density functional theory calculations to examine the stability of nitrogen-doped wurtzite ZnO under pressure.